Altered mannose metabolism in chronic stress and depression is rapidly reversed by vitamin B12 - Franzka, Patricia; Turecki, Gustavo; Cubillos, Susana; Kentache, Takfarinas; Steiner, Johann; Walter, Martin; Hübner, Christian A.; Engmann, Olivia (Frontiers in Nutrition, 2022)
GDP-Mannose Pyrophosphorylase B (GMPPB) is a key enzyme for glycosylation. Previous studies suggested a dysregulation of GMPBB and mannose in depression. Evidence, however, was sporadic and interventions to reverse these changes are unknown. Here, we show that GMPPB protein, but not RNA abundance is increased in the postmortem prefrontal cortex (PFC) of depressed patients and the chronic variable stress (CVS) mouse-model. This is accompanied by higher plasma mannose levels. Importantly, a single dose of intraperitoneally administered vitamin B12, which has previously been shown to rapidly reverse behavioral symptoms and molecular signatures of chronic stress in mice, normalized GMPPB plasma mannose levels and elevated GDP-mannose abundance. In summary, these data underline metabolic dysregulation in chronic stress and depression and provide further support for rapid effects of vitamin B12 on chronic stress.